Novel LAT Pathogenic Variants in a POI Family and Its Role in the Ovary - Chu, Kun; He, Yi; Li, Ziyuan; Jiang, Zhongxin; Wang, Liang; Ji, Yixuan; Wang, Xiang; Pang, Wenjuan; Sun, Ningxia; Yang, Fu; Li, Wen (Frontiers in Genetics, 2021)
Premature ovarian insufficiency (POI) affects about 1% of women under 40 years and leads most often to definitive infertility with adverse health outcomes. Genetic factor has been reported to play an important role in POI. However, the genetic etiology remains unknown in the majority of the POI patients. Whole-exome sequencing and variant analysis were carried out in a POI pedigree. In vitro studies of the wild-type and mutant proteins were conducted in primary granulosa cells (GCs) and granulosa cell line. The result showed that the patients carried compound heterozygous nonsynonymous mutations (c.245C>T and c.181C>G) in LAT gene, which were identified to be transmitted from her parents. The two variants were assessed to affect residues that were conserved across different species examined, and were predicted to be deleterious by software predictions. Protein structure predicting result indicated that the two variants could alter their interactions with surrounding residues, which may change the internal structure of the LAT protein. Moreover, LAT protein expression in GCs were demonstrated for the first time, and further functional assays suggested that this mutation could reduce LAT expression and influence GC survival, which may contribute to the etiology of POI. In summary, we detect novel LAT pathogenic variants in a POI pedigree and report for the first time that LAT is present and functional in the GCs of the ovary. Our findings not only shed new light on the role of LAT in GCs, but also broaden the spectrum of genetic causes of POI.